Degradation of D-2-hydroxyglutarate in the presence of isocitrate dehydrogenase mutations - Berger, Raffaela S. (Sci Rep, 2019)
D-2-Hydroxyglutarate (D-2-HG) is regarded as an oncometabolite. It is found at elevated levels in certain malignancies such as acute myeloid leukaemia and glioma. It is produced by a mutated isocitrate dehydrogenase IDH1/2, a low-affinity/high-capacity enzyme. Its degradation, in contrast, is catalysed by the high-affinity/low-capacity enzyme D-2-hydroxyglutarate dehydrogenase (D2HDH). So far, it has not been proven experimentally that the accumulation of D-2-HG in IDH mutant cells is the result of its insufficient degradation by D2HDH. Therefore, we developed an LC-MS/MS-based enzyme activity assay that measures the temporal drop in substrate and compared this to the expression of D2HDH protein as measured by Western blot. Our data clearly indicate, that the maximum D-2-HG degradation rate by D2HDH is reached in vivo, as v(max) is low in comparison to production of D-2-HG by mutant IDH1/2. The latter seems to be limited only by substrate availability. Further, incubation of IDH wild type cells for up to 48 hours with 5 mM D-2-HG did not result in a significant increase in either D2HDH protein abundance or enzyme activity.